Directive Illocutionary Acts in a Child’s Utterances in the Sea Beast Movie 2022 - Khoirotusyarifah; Dedi Sulaeman; Muhammad Aminuddin; Sajidin (Institut Agama Islam Negeri Palopo, 2025)
Children's language is unique and has its own characteristics. It’s unique because the utterance children produce has hidden meanings that are not understood. In this line, when a child asks something, it does not mean that the child is asking, but it could be that the meaning of the utterance is requesting something. This research was intended to discover the types and function in a child’s utterances that were found in the movie. It was descriptive qualitative research. The data in this study was in the form of an utterance used by a child in The Sea Beast. The illocutionary acts theory was used to answer the questions of this research. It includes the theory proposed by Searle (1976). Based on the analysis, the researcher found a directive illocutionary acts as one of characteristics of a child language. It is found the act function to express what the speaker wants such as requesting, asking, begging, commanding, advising, warning, inviting, and suggesting. As well as asking act is most commonly found in this function. Keywords: a child’s utterances, directive, illocutionary acts